A Metatheory for Cognitive Development (or "Piaget is Dead" Revisited). Issue 6 (16th January 2018) - Bjorklund, David F.
Abstract : In 1997, I argued that with the loss of Piaget's theory as an overarching guide, cognitive development had become disjointed and a new metatheory was needed to unify the field. I suggested developmental biology, particularly evolutionary theory, as a candidate. Here, I examine the increasing emphasis of biology in cognitive development research over the past 2 decades. I describe briefly the emergence of evolutionary developmental psychology and examine areas in which proximal and distal biological causation have been particularly influential. I argue that developmental biology will continue to increasingly influence research and theory in cognitive development and that evolutionary theory is well on its way to becoming a metatheory, not just for cognitive development, but for developmental psychology generally.